Water supply and pollution control - Clark, John W. (International Textbook Co., 1965)
This book provides practicing engineers with water-based environment engineering from theory to practice by presenting the principles of water treatment, wastewater treatment, water reuse, water quality, and overviews of regulations regarding pollution control and drinking water quality.